Preparation method and application of biodegradable multifunctional chitosan hydrogel

By using biodegradable hydrogels composed of chitosan, vanillin and sodium lignin sulfonate, the problem of poor antibacterial properties of traditional dressings is solved, and better antibacterial, antioxidant properties and biocompatibility are achieved, providing Safe and effective wound dressing.

CN119303150APending Publication Date: 2025-01-14NANJING FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310854499.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Traditional medical trauma dressings have poor antibacterial and antioxidant properties, and conventional polymer antibacterial hydrogels have potential environmental safety and biosafety risks.

Method used

A biodegradable chitosan hydrogel is used, which consists of chitosan, vanillin and sodium lignin sulfonate. The hydrogel is formed by mixing in acetic acid solution at room temperature and waiting for crosslinking.

Benefits of technology

Significantly improves antibacterial, antioxidant and biocompatible, providing a non-toxic and harmless biodegradable material suitable as an ideal wound dressing, promoting wound healing and reducing the risk of microbial invasion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303150A_ABST
    Figure CN119303150A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of biodegradable multifunctional chitosan hydrogel. The multifunctional hydrogel mainly comprises the following components: chitosan, vanillin and sodium lignin sulfonate. An in-vitro antibacterial test shows that the prepared chitosan / vanillin / sodium lignin sulfonate hydrogel has relatively strong antibacterial ability to gram-positive bacteria and gram-negative bacteria, and an antioxidant result shows that the chitosan / vanillin / sodium lignin sulfonate hydrogel has a relatively strong scavenging effect on nitrogen free radicals. In-vitro experiment results of mouse fibrocytes show that the hydrogel has no biotoxicity and can promote proliferation of the fibrocytes to a certain extent, so that the effect of promoting wound healing is achieved. The results show that the chitosan / vanillin / sodium lignin sulfonate hydrogel has excellent antibacterial property, oxidation resistance and biocompatibility, the preparation process is simple, and the chitosan / vanillin / sodium lignin sulfonate hydrogel has commercial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical polymer materials, and in particular to a preparation method and application of a biodegradable multifunctional chitosan hydrogel. Background Art

[0002] The skin is the largest organ in the human body, which protects against external injuries and pathogens. Every year, tens of thousands of people are affected by acute and chronic skin injuries. The inflammatory state after skin injury can lead to slow local tissue healing or even necrosis. Various metabolites that appear in the early stages of wound healing, such as tissue fluid, proteins and dead cells, increase the probability of microbial infection of the wound. An ideal wound dressing can serve as a protective barrier to prevent further damage to the wound and prevent microorganisms from invading the wound. It can also absorb wound exudate, remove metabolites and serve as a medium for gas exchange between the wound surface and the outside world. In addition to flexibility and mechanical stability, an ideal wound dressing needs to exhibit appropriate anti-inflammatory, antioxidant and antibacterial properties.

[0003] Traditional wound dressings such as absorbent cotton and gauze do not have good antibacterial properties and are not suitable for all wound types. Antimicrobial drugs used in wound dressings can be divided into three types: antibiotics, nanoparticles, and natural biomaterials. Nanoparticles such as silver and zinc oxide nanoparticles are considered to be effective alternatives to traditional antibiotics. Natural biomaterials such as sericin, alginate, and chitosan have good antibacterial properties and good biocompatibility. Studies have shown that under moist conditions, the wound closure rate is almost twice that under dry conditions. Therefore, dry absorbent cotton and gauze dressings are gradually replaced by wet dressings. Hydrogels are considered to be an ideal alternative to traditional dry wound dressings in wet dressings.

[0004] Chitosan is a natural polysaccharide obtained by deacetylation of chitin. It is non-toxic, biodegradable and has broad-spectrum antibacterial properties. Vanillin can be prepared from lignin, a by-product of papermaking, and has anti-tumor, antioxidant and anti-mutagenic properties. The amino group in the chitosan structure reacts with vanillin through Schiff base reaction to form a hydrogel with certain mechanical properties, antibacterial properties and antioxidant properties. The gel formation time is short and the biocompatibility is good, making it an ideal wound dressing. Sodium lignin sulfonate is a natural polyphenol compound derived from papermaking by-products. It has the characteristics of low cost, antioxidant properties, biodegradability and good biocompatibility. Its introduction into hydrogel biological dressings can improve the mechanical properties and antioxidant properties of the original dressings to a certain extent. Summary of the invention

[0005] Aiming at the shortcomings of poor antibacterial and antioxidant properties of traditional medical wound dressings and potential environmental safety and biosafety risks of conventional high-molecular antibacterial hydrogels, the present invention provides a biodegradable chitosan hydrogel and a preparation method and application thereof.

[0006] In order to solve the above problems, the first aspect of the present invention provides a biodegradable chitosan hydrogel, which mainly comprises the following components: chitosan, vanillin, and sodium lignin sulfonate.

[0007] Preferably, by weight, the content of chitosan is 4-8wt%, the content of vanillin is 2-5w%, and the content of sodium lignin sulfonate is 0.2-0.5wt%.

[0008] Preferably, the chitosan (C) is analytically pure and has a deacetylation degree of ≥95%.

[0009] Preferably, the vanillin (V) is analytically pure.

[0010] Preferably, the sodium lignin sulfonate (L) is analytically pure.

[0011] Compared with the prior art, the biodegradable chitosan hydrogel provided by the present invention has the following beneficial effects:

[0012] 1) The raw materials used are biomass and its derivatives, which are non-toxic and harmless and have obvious antibacterial effects

[0013] 2) Compared with chitosan / sodium lignin sulfonate hydrogel and chitosan / vanillin hydrogel, chitosan / vanillin / sodium lignin sulfonate hydrogel has better antibacterial, antioxidant and biocompatibility properties.

[0014] The second aspect of the present invention provides a method for preparing the chitosan / sodium lignin sulfonate hydrogel (LC), chitosan / vanillin hydrogel (CV), and chitosan / vanillin / sodium lignin sulfonate (LCV) having the above-mentioned effect 2, comprising the following steps:

[0015] S1. Add appropriate amount of chitosan and sodium lignin sulfonate to 1% acetic acid solution at room temperature and stir thoroughly for half an hour.

[0016] S2. Dissolve an appropriate amount of vanillin in anhydrous ethanol at room temperature;

[0017] S3, the two solutions obtained in step S1 and S2 are mixed and fully stirred, poured into the mold and allowed to stand for 30 minutes to wait for the hydrogel to be fully cross-linked

[0018] Compared with the prior art, the method for preparing the biodegradable chitosan hydrogel provided by the present invention has the following beneficial effects:

[0019] 1) Vanillin and sodium lignin sulfonate, as derivatives of lignin, have good biocompatibility. The hydroxyl groups on their benzene rings can effectively remove free radicals around the wound and promote wound healing.

[0020] 2) Chitosan contains cations, which can effectively inhibit bacteria without causing drug resistance

[0021] 3) The Schiff base produced by cross-linking vanillin and chitosan can synergize with chitosan to exert antibacterial effects BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the cross-linking mechanism of LCV hydrogel in Example 1;

[0023] Figure 2 The infrared spectra of the hydrogels of LC, CV, LCV-1, LCV-2 and LCV-3 in Example 2;

[0024] Figure 3 These are SEM scanning electron micrographs of LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels of Example 3.

[0025] FIG4 is a graph showing the compressive stress-strain test of LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels of Example 4

[0026] Figure 5 DPPH free radical removal effect diagram of LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels of Example 5

[0027] Figure 6 The inhibitory effect of LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels of Example 6 on Gram-negative bacteria and Gram-positive bacteria is shown in FIG.

[0028] Figure 7 The cell activity graph of LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels of Example 7 co-cultured with mouse L929 fibroblasts for 24 hours DETAILED DESCRIPTION

[0029] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0030] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0031] The embodiment of the present invention provides an antibacterial and antioxidant hydrogel that can be used as a medical dressing, comprising the following components: polyvinyl alcohol, chitosan hydrochloride, and vanillin, wherein the chitosan content is 4-8wt%, the vanillin content is 2-5wt%, and the sodium lignin sulfonate content is 0.2-0.5wt%.

[0032] Example 1

[0033] Preparation of LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels

[0034] S1. Add appropriate amount of chitosan and sodium lignin sulfonate to 1% acetic acid solution at room temperature and stir thoroughly for half an hour.

[0035] S2, the solution obtained in step S1 is mixed and stirred thoroughly, poured into a mold, and allowed to stand for 30 minutes to wait for the hydrogel to be fully cross-linked to obtain chitosan / sodium lignin sulfonate hydrogel (LC)

[0036] S3, dissolving an appropriate amount of vanillin in anhydrous ethanol at room temperature;

[0037] S4, the two solutions obtained in step S1 and S3 are mixed and fully stirred, poured into a mold and allowed to stand for 30 minutes to wait for the hydrogel to be fully cross-linked to obtain chitosan / vanillin / sodium lignin sulfonate hydrogel (LCV-1, LCV-2, LCV-3)

[0038] S5. At room temperature, use 1% acetic acid solution as solvent, add an appropriate amount of chitosan, stir thoroughly for half an hour, add the vanillin solution obtained in S3, stir thoroughly, pour into the mold and let stand for 30 minutes to wait for the hydrogel to be fully cross-linked to obtain chitosan / vanillin hydrogel (CV)

[0039] In a specific embodiment, the preparation method is simple in steps, mild and controllable, the prepared hydrogel is non-toxic and harmless and has obvious antibacterial effect, the main body of the hydrogel is chitosan, which has good gelling properties with vanillin and sodium lignin sulfonate, and its cross-linking mechanism is as follows Figure 1 As shown. It is an ideal material for medical dressing. The present invention will be described in detail below through specific embodiments.

[0040] Example 2

[0041] FTIR spectra of LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels

[0042] The groups of LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels were characterized by FTIR spectrometer. First, LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels were freeze-dried using a vacuum freeze dryer. Then, the freeze-dried LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels were uniformly mixed with potassium bromide to form ultrafine particles, which were then compressed using a tablet press and then tested by FTIR. Figure 2 As shown, CV, LCV-1, LCV-2, and LCV-3 hydrogels have a peak at 1605 cm -1 The stretching vibration peak of the C=N bond, which is not present in LC hydrogel, is clearly visible, indicating that there is a cross-linking reaction between the amino group of chitosan and the aldehyde group of vanillin.

[0043] Example 3

[0044] SEM scanning electron microscope test of LC, CV, LCV-1, LCV-2, LCV-3

[0045] The prepared LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels were frozen and placed in a freeze dryer for freeze drying, and then subjected to SEM scanning electron microscopy testing. Figure 3 As shown, it can be seen that the pore size of the Schiff base network formed by CV is larger than that of the network formed by LC. With the addition of sodium lignin sulfonate, the pore size of the network gradually increases. Moreover, the pores of CV, LCV-1, LCV-2, and LCV-3 are relatively rough, which is conducive to the attachment of wound cells and the proliferation of cells, thereby achieving the purpose of promoting wound healing.

[0046] Example 4

[0047] Compressive stress-strain tests of LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels

[0048] The prepared LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels were placed in a universal testing machine to test their compressive strain and compressive stress. Figure 4-1 As shown in the figure, the mechanical properties of the Schiff base network of CV hydrogel are significantly better than the hydrogen bond network structure of LC hydrogel. With the introduction of sodium lignin sulfonate in Schiff base hydrogel, its mechanical properties also show a positive correlation with the amount of sodium lignin sulfonate added. Among them, LCV-3 hydrogel can still maintain a good internal structure when the compression strain reaches 50%, which is better than LC, CV, LCV-1, and LCV-2 hydrogels. Then, LCV-3 hydrogel was subjected to compression rebound test, with the strain set to 30% and the number of cycles set to 20. The results are shown in the figure. Figure 4-2 As shown, it can be seen that after the cyclic rebound test, the LCV-3 hydrogel can still maintain a good structure, showing its excellent mechanical properties.

[0049] Example 5

[0050] LC, CV, LCV-1, LCV-2, LCV-3 hydrogel antioxidant test

[0051] First, weigh 0.016g 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) and dissolve it in 40ml anhydrous ethanol for later use. Weigh 500mg LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels respectively and put them into test tubes. Add 5ml DPPH solution to each test tube, keep it away from light for 24h, then centrifuge it, and then test its ultraviolet absorption light value. The results are as follows: Figure 5 Take the absorbance value corresponding to 517nm wavelength according to the formula The free radical removal rates of each were calculated and their antioxidant effects were compared. The results are shown in the following table:

[0052] sample LC CV LCV-1 LCV-2 LCV-3 Removal rate 92.41% 86.39% 92.69% 93.12% 93.27

[0053] Example 6

[0054] Antibacterial effect test of LC, CV, LCV-1, LCV-2 and LCV-3 hydrogels

[0055] The purchased Escherichia coli lyophilized powder and Staphylococcus aureus lyophilized powder were mixed with the matching broth for bacterial recovery, 2.5g LB powder was dissolved in 100ml deionized water, and then 1.3g agar powder was added and evenly dissolved. Then, the mixture was placed in an autoclave and sterilized at 121 degrees Celsius for 20 minutes to prepare a sterile solid culture medium for use. The sterilized solid culture medium was cooled to 40-50 degrees Celsius and poured into a bacterial culture dish. After solidification, the two bacteria were streaked on the plate and then cultured at 37 degrees Celsius for 24 hours. The cultured bacteria were taken out, and the better strains were placed in the liquid culture medium for constant temperature shaking culture for 10-14 hours to prepare the bacterial suspension. Finally, the prepared bacterial suspension was taken out, and 20 microliters of the bacterial suspension were mixed evenly with the solid culture medium. After the mixture of the culture medium and the bacterial suspension solidified, LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels were placed and cultured at a constant temperature of 37 degrees Celsius for 24 hours. The inhibitory effects on Escherichia coli and Staphylococcus aureus were observed. Figure 6 As shown in the figure, it can be seen that the LC hydrogel has no obvious inhibition zone, and the inhibition effect of the CV hydrogel is significantly better than that of the LC, LCV-1, LCV-2, and LCV-3 hydrogels. On the basis of CV, as the addition amount of sodium lignin sulfonate increases, the diameter of the inhibition zone also increases. The results are shown in the following table:

[0056]

[0057] Example 7

[0058] Biocompatibility testing of LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels

[0059] The LC, CV, LCV-1, LCV-2, and LCV-3 hydrogels prepared in Example 1 were made into 10% aqueous solutions, and then 10 μL of the hydrogel aqueous solution was added to 90 μL of the cell suspension, and then 100 μL of the above hydrogel and cell suspension were added to a 96-well plate and co-cultured in a 37°C constant temperature carbon dioxide incubator (containing 5% CO2) for 24 hours. After 24 hours, the well plate was taken out, washed twice with PBS solution, 10 μL of CCK-8 working solution and 90 μL of cell culture medium were added to each well, and incubated in a 37°C constant temperature carbon dioxide incubator (containing 5% CO2) for 1 to 2 hours, and then the absorbance (OD) was measured at a wavelength of 450 nm using an enzyme marker, and the cell survival rate was calculated according to the formula: Cell survival rate (%) = OD 实验组 / OD 对照组 × 100%. The result is Figure 7 As shown, the number of cells in each group determined by CCK-8 assay increased over time without inter-group differences. This indicates that the hydrogel has good biocompatibility and can be used for in vivo applications. The cell survival rate is shown in the following table:

[0060] sample LC CV LCV-1 LCV-2 LCV-3 Survival rate 103.4% 103.8% 95.9% 103.8% 97.7%

Claims

1. A biodegradable multifunctional chitosan-based hydrogel, characterized in that: The invention mainly comprises the following components: chitosan, vanillin and sodium lignin sulfonate.

2. The biodegradable multifunctional chitosan hydrogel according to claim 1, characterized in that: By weight, the content of chitosan is 4-8wt%, the content of vanillin is 1-3wt%, and the content of sodium lignin sulfonate is 0.2-0.5wt%.

3. The biodegradable multifunctional chitosan hydrogel according to claim 2, characterized in that: The deacetylation degree of the chitosan is ≥95%.

4. The biodegradable multifunctional chitosan hydrogel according to claim 1 or 2, characterized in that: The amino group in the chitosan and the aldehyde group of vanillin generate a Schiff base structure.

5. The biodegradable multifunctional chitosan hydrogel according to claim 1 or 2, characterized in that: The vanillin and sodium lignin sulfonate are both analytically pure reagents.

6. A method for preparing the biodegradable multifunctional chitosan hydrogel according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Add appropriate amount of chitosan and sodium lignin sulfonate to 1% acetic acid solution at room temperature and stir thoroughly for half an hour. S2. Dissolve an appropriate amount of vanillin in anhydrous ethanol at room temperature; S3, mixing the two solutions obtained in step S1 and S2, stirring thoroughly, pouring into a mold and letting it stand for 30 minutes to wait for the hydrogel to be fully cross-linked.

7. The use of the antibacterial and antioxidant hydrogel according to any one of claims 1 to 6, characterized in that: The biodegradable multifunctional chitosan hydrogel is used as a medical dressing for wound treatment.